Non‐toxic luminescent carbon dot/poly(dimethylacrylamide) nanocomposite reagent for latent fingermark detection synthesized via surface initiated reversible addition fragmentation chain transfer polymerization. Issue 7 (13th January 2015) - Dilag, Jessirie; Kobus, Hilton; Yu, Yang; Gibson, Christopher T; Ellis, Amanda V
<x xml:space="preserve">Abstract</x> The development of non‐toxic fluorescent nanocomposites for latent fingermark detection is crucial for implementation into the forensic sciences. Carbon dots with an adhesive poly(dimethylacrylamide) coating show not only fluorescence but allowed for color‐selective fluorescence exploited with appropriate filters upon visualization, and photographing of the developed fingermarks.